2013
DOI: 10.1037/mil0000019
|View full text |Cite
|
Sign up to set email alerts
|

Confidentiality and Mental Health/Chaplaincy Collaboration

Abstract: Confidentiality can both facilitate and inhibit working relationships of chaplains and mental health professionals addressing the needs of service members and veterans in the United States. Researchers conducted this study to examine opportunities for improving integration of care within the Department of Defense (DoD) and Department of Veterans Affairs (VA). Interviews were conducted with 198 chaplains and 201 mental health professionals in 33 DoD and VA facilities. Using a blended qualitative research approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Particularly in the military where fears persist about mental health treatment potentially leading to negative career repercussions or perceptions that one is weak, chaplains are often considered a safer, trusted, and more confidential option. 21,22 Veterans and service members may also seek out chaplains because chaplains are able to address salient spiritual dynamics related to depression, posttraumatic stress disorder (PTSD), and other common psychiatric problems. For instance, research suggests that PTSD severity, chronicity, and treatment seeking are often interwoven with issues of guilt, 23,24 forgiveness, 25,26 religious faith, [27][28][29] meaning and purpose, 27,30 and moral injury.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in the military where fears persist about mental health treatment potentially leading to negative career repercussions or perceptions that one is weak, chaplains are often considered a safer, trusted, and more confidential option. 21,22 Veterans and service members may also seek out chaplains because chaplains are able to address salient spiritual dynamics related to depression, posttraumatic stress disorder (PTSD), and other common psychiatric problems. For instance, research suggests that PTSD severity, chronicity, and treatment seeking are often interwoven with issues of guilt, 23,24 forgiveness, 25,26 religious faith, [27][28][29] meaning and purpose, 27,30 and moral injury.…”
Section: Introductionmentioning
confidence: 99%
“…For some veterans, the chaplain was the only person they could talk to in confidence during their service; VA chaplains by contrast tend to operate more as part of clinical teams, with different expectations around confidentiality based on this different context. 23 Thus, while not all veterans will be interested in seeing a chaplain, VHA chaplains may be, for many veterans, the preferred point of contact for multiple forms of distress. MHICS equips chaplains to be prepared to address the wide range of psychosocial distress that they regularly encounter among service members and veterans.…”
Section: Organizational and Personal Contextmentioning
confidence: 99%
“…MHICS equips chaplains to be prepared to address the wide range of psychosocial distress that they regularly encounter among service members and veterans. 14 , 21 Given that chaplains are the preferred and trusted point of contact for many, 23 chaplains are uniquely suited to inform the rest of the healthcare system about profound struggles some veterans face, including moral injury and suicidality. Furthermore, chaplains are distinctively suited to lead the way in addressing those struggles, especially when equipped with training in evidence-based psychosocial approaches to care.…”
Section: Organizational and Personal Contextmentioning
confidence: 99%
“…Zinzow et al [ 22 ] found that concerns of confidentiality also keep many military members from seeking help, especially those in active service. Bulling et al [ 23 ] suggested that military members who choose to seek help from chaplains rather than others likely do so because of the strict confidentiality that chaplains abide by. But the lack of exploratory studies focusing on military cadets and their help-seeking behaviors reflects a void in today’s literature.…”
Section: Introductionmentioning
confidence: 99%